Jubileusze Profesorów Andrzeja Nadolskiego i Jerzego Kmiecińskiego - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
ln 1992 two important jubilee conferences were arranged by the Department of Archaeology of Łódź University. The first jubilee session was held on 7th-8th May on the occasion of the seventieth birthday anniversary of Professor Dr. hab. Andrzej Nadolski. The whole archaeological milieu of Łódź was involved in organizing the conference, the Łódź Branch of the Scientific Society of Polish Archaeologists being particularly active. The session was held in the Archaeological and Ethnographic Museum in Łódź, and the papers read usually dealt with military matters (notably arms and armour) which are the special subject of Professor Nadolski. Most papers were published in a volume entitled Arma el ollae. The second session was held on 20th November in the conference centre of Łódź University on the occasion of the 40th anniversary of the scholarly activity of Professor Dr. hab. Jerzy Kmieciński. Several papers were read, and Professor Kmiedński was presented with the jubilee edition of Folia Archaeologica, ,Acta Universitatis Lodziensis”, vol. XVI, which contained papers dedicated to him. However, these events do not mark the end of the scholarly activity of the two Professors. They both are still active, deeply involved in scholarly and didactic activities, and concerned with the development of the Łódź archaeological centre.